The Policy-Making Process in the Old Chilean Democracy - Olavarria-Gambi, M (Bellwether Publishing, Ltd., 2021)
Asking how public policies were made in the old Chilean democracy, this article analyzes the public administration reform of the 1920s and the creation of Chile’s National Health Service in 1952. Collected evidence shows that the policy-making process may be characterized as elitist, technocratic, and where the president s motivation toward a particular issue plays a key role for the issue to be included in the government agenda and go further in the process. This is very similar to how the policy process of the new Chilean democracy has been characterized. Considering that under Pinochet’s dictatorship deep reforms were introduced in political institutions and that following the new institutionalism framework, rule behaviors, and interchange of policy actors, the article finishes asking what other factors may be acting on a political institution or the policy process directly to explain the similarity between this finding. © 2020 Taylor & Francis Group, LLC.